Evaluation of the efficacy of auricular acupressure in preventing depression in adolescents with insomnia: study protocol for a randomized controlled trial - Lian, Xiaoyang; Zhang, Yuting; Xu, Min; Li, Xiaojie; Li, Guoyu; Wang, Xiaoying; Qin, Shan; Ye, Junlan; Liu, Chengyong (Frontiers in Psychiatry, 2025)
BackgroundInsomnia and depression represent prevalent issues during adolescence. Auricular acupressure (AA), a simple, low-cost traditional Chinese medicine therapy with minimal adverse effects, has demonstrated efficacy in improving sleep quality and alleviating depressive symptoms in adult populations. However, existing research has predominantly focused on adults, with limited evidence regarding AA’s effectiveness in improving sleep and preventing depression among adolescents.MethodsThis study is a single-center, double-blind, randomized controlled trial conducted in Nanjing, China. Participants are students from junior and senior high schools in Nanjing. A multi-stage stratified cluster sampling method is used to recruit students from 7th and 8th grades (junior high) and 10th and 11th grades (senior high). Baseline data will be collected using the Chinese version of the Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI), Adolescent Sleep Hygiene Scale (ASHS), Children’s Depression Inventory (CDI), Adolescent Self-rating Life Events Checklist (ASLEC) and Adolescent Sleep-Wake Scale (ASWS), and insomnia patients will be identified. Adolescents who met the inclusion and exclusion criteria and whose guardians signed informed consent forms will be enrolled in the study. They will be randomly assigned to one of three groups: AA group, sham auricular acupressure (SAA) group, and control group. The treatment lasted for 8 weeks, with follow-up assessments at 3 and 6 months post-treatment. The primary outcome measures are PSQI and BDI scores, while secondary outcome measures included ASHS, CDI, ASLEC, and ASWS scores.DiscussionThis prospective study evaluates AA’s efficacy in enhancing sleep quality and preventing depression in adolescents. The findings will elucidate AA’s potential clinical applications for adolescent insomnia treatment and depression prevention, thereby providing evidence to support its broader implementation in this population.Clinical trial registrationhttp://itmctr.ccebtcm.org.cn/, identifier ITMCTR2024000343.